2012
DOI: 10.1152/ajpgi.00429.2011
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic and myogenic motor patterns of rabbit proximal, mid, and distal colon

Abstract: Dinning PG, Costa M, Brookes SJ, Spencer NJ. Neurogenic and myogenic motor patterns of rabbit proximal, mid, and distal colon. Am J Physiol Gastrointest Liver Physiol 303: G83-G92, 2012. First published May 3, 2012 doi:10.1152/ajpgi.00429.2011The rabbit colon consists of four distinct regions. The motility of each region is controlled by myogenic and neurogenic mechanisms. Associating these mechanisms with specific motor patterns throughout all regions of the colon has not previously been achieved. Three sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(104 citation statements)
references
References 43 publications
10
93
1
Order By: Relevance
“…Ripples persisted in all individuals following neuronal blockade, similar to the 'myogenic ripples' described in numerous mammalian studies (Benard et al, 1997;D'Antona et al, 2001;Dinning et al, 2012;Hennig et al, 2010a;Huizinga et al, 2011). However, instead of the fairly constant frequency seen under control conditions, the prevalence of lower-frequency ripples was markedly increased.…”
Section: Role Of Icc In the Control Of Gastrointestinal Motility In Fishsupporting
confidence: 67%
See 1 more Smart Citation
“…Ripples persisted in all individuals following neuronal blockade, similar to the 'myogenic ripples' described in numerous mammalian studies (Benard et al, 1997;D'Antona et al, 2001;Dinning et al, 2012;Hennig et al, 2010a;Huizinga et al, 2011). However, instead of the fairly constant frequency seen under control conditions, the prevalence of lower-frequency ripples was markedly increased.…”
Section: Role Of Icc In the Control Of Gastrointestinal Motility In Fishsupporting
confidence: 67%
“…Ripples primarily propagated in an oral direction, which has been suggested to promote or optimize absorption (Chen et al, 2013;Dinning et al, 2012;Hennig et al, 2010a), as the contractions may aid in the mixing and circulation of intestinal contents over the mucosal surface of the gastrointestinal tract (Lee, 1983). Ripples persisted in all individuals following neuronal blockade, similar to the 'myogenic ripples' described in numerous mammalian studies (Benard et al, 1997;D'Antona et al, 2001;Dinning et al, 2012;Hennig et al, 2010a;Huizinga et al, 2011).…”
Section: Role Of Icc In the Control Of Gastrointestinal Motility In Fishmentioning
confidence: 84%
“…Our experimental setup was based on those described previously (14). The oral ends of the preparations were cannulated via an L-shaped plastic connector, through which warmed Krebs solution could be infused by a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%
“…colon motility; enteric neurons; spatiotemporal maps; peristalsis COLONIC MOTILITY IS CONTROLLED by complex interactive processes in the gut, involving both nerve cells (neurogenic) and spontaneous muscle activity (myogenic). A number of studies have characterized fundamental mechanisms in the colon of the guinea pig, mouse, and rabbit and have shown that propagating contractions underlying peristalsis, or other propulsive motor patterns, require activity in the enteric nervous system (8,11,13,14,17,25).…”
mentioning
confidence: 99%
“…Ripples are the most prevalent contraction type in the small and large intestine of mammals such as guinea pigs, rats and rabbits (Benard et al, 1997;D'Antona et al, 2001;Dinning et al, 2012;Hennig et al, 2010;Huizinga et al, 2011), but this is the first time this contraction type has been described in live adult fish. The role of ripples is not clearly understood, but it has been suggested that they could promote or optimise absorption (Chen et al, 2013;Dinning et al, 2012;Hennig et al, 2010) by mixing/circulating the intestinal contents over the mucosal surface of the gastrointestinal tract (Lee, 1983). The lower frequency and velocity of ripples in shorthorn sculpin compared with mammals can probably be accounted for by differences in temperature (sculpin experiments were performed at 10°C compared with 37°C in most mammalian studies) and thermoregulation strategies (ectothermic versus endothermic) of the respective classes.…”
Section: Do Myogenic Ripples Represent Slow Wave Activity?mentioning
confidence: 97%